Life cycle of Triatoma ryckmani (Hemiptera: Reduviidae) in the laboratory, feeding patterns in nature and experimental infection with Trypanosoma cruzi - Zeledón, Rodrigo (2010)
A cohort initiated with 121 eggs, yielding 105 first instar nymphs (eclosion rate: 86.78%), allowed us to observe the entire life cycle of Triatoma ryckmani under laboratory conditions (24ºC and 62% relative humidity), by feeding them on anesthetized hamsters. It was possible to obtain 62 adults and the cycle from egg to adult took a mean of 359.69 days with a range of 176-529 days (mortality rate of nymphs: 40.95%). Mean life span of adults was of 81 days for females and 148 days for males. The developmental periods of 4th and 5th nymphs were longer than those of the other instars. This suggests that young siblings have a better chance of taking a hemolymph meal from older ones, in order to survive during fasting periods during prolonged absences of vertebrate hosts from natural ecotopes. The stomach contents of 37 insects showed blood from rodents (15 cases), lizards (7 cases), birds (6 cases) and insect hemolymph (7 cases). Out of 10 insects fed by xenodiagnosis on a Trypanosoma cruzi infected mouse, all but one became infected with the parasite.